2011
DOI: 10.1007/s10048-011-0279-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlations in sepiapterin reductase deficiency. A splicing defect accounts for a new phenotypic variant

Abstract: Sepiapterin reductase (SR) catalyzes the final step in the de novo synthesis of tetrahydrobiopterin, essential cofactor for phenylalanine, tyrosine, and tryptophan hydroxylases. SR deficiency is a very rare disease resulting in monoamine neurotransmitter depletion. Most patients present with clinical symptoms before the first year of age corresponding to a dopa-responsive dystonia phenotype with diurnal fluctuations, although some patients exhibit more complex motor and neurological phenotypes. Herein, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 27 publications
0
32
1
Order By: Relevance
“…[80][81][82][83][84] Sepiapterin reductase deficiency is characterized by axial hypotonia, delays in the development of motor function and language, oculogyric crises, muscle weakness, and dystonia. 81,[82][83][84][85][86][87] Patients with mutations in SPR are commonly misdiagnosed with cerebral palsy. 84 As in GTP-CH-I deficiency, the symptoms can fluctuate diurnally; 81,86,87 in one review of published cases, marked diurnal variation of motor abnormalities was observed in nine of 11 patients, 87 although diurnal variation might be difficult to identify in infants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[80][81][82][83][84] Sepiapterin reductase deficiency is characterized by axial hypotonia, delays in the development of motor function and language, oculogyric crises, muscle weakness, and dystonia. 81,[82][83][84][85][86][87] Patients with mutations in SPR are commonly misdiagnosed with cerebral palsy. 84 As in GTP-CH-I deficiency, the symptoms can fluctuate diurnally; 81,86,87 in one review of published cases, marked diurnal variation of motor abnormalities was observed in nine of 11 patients, 87 although diurnal variation might be difficult to identify in infants.…”
Section: Introductionmentioning
confidence: 99%
“…81,[82][83][84][85][86][87] Patients with mutations in SPR are commonly misdiagnosed with cerebral palsy. 84 As in GTP-CH-I deficiency, the symptoms can fluctuate diurnally; 81,86,87 in one review of published cases, marked diurnal variation of motor abnormalities was observed in nine of 11 patients, 87 although diurnal variation might be difficult to identify in infants. 84 The severity of the condition varies according to the nature of the genetic defect and consequent enzymatic defect, but symptoms improve with levodopa treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Prolactin levels can also help in monitoring the medication (2,8,12,(15)(16)(17)(18)(19)(20)(21)(22)(23)25).…”
Section: Discussionmentioning
confidence: 99%
“…This disorder is classified as a neurotransmitter disorder (3,4,13,14). The clinical hallmarks of this rare, but probably underdiagnosed disorder are disease onset most often before 1 year of age with paroxysmal stiffening, upward gaze, and hypotonia (2,8,12,(15)(16)(17)(18)(19)(20)(21)(22)(23). Cognitive symptoms, speech disturbances, motoric delay, and dystonic movements with diurnal fluctuations are frequently seen, but normally occur later in the disease course.…”
mentioning
confidence: 99%
“…Deficiency of any of these three enzymes (GTPCH, SR or TH) leads to dopamine depletion at the synaptic terminals within the basal ganglia, causing both motor and non-motor dysfunction (mood swings, depression, verbal memory deficits and concentration problems) 7 8. There is pathological and biochemical evidence of striatal dopamine deficiency in DRDs to support this hypothesis 9 10…”
Section: When To Suspect Drd?mentioning
confidence: 99%